2010
DOI: 10.4028/www.scientific.net/kem.449.9
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Indentation on AISI 1018 Borided Steels

Abstract: Fracture indentation was applied to estimate the fracture toughness of AISI 1018 borided steels. The Fe2B hard layers were formed using the powder-pack boriding process for two temperatures with 4 and 8 h of exposure times. The fracture toughness of the iron boride layer of the AISI 1018 borided steels was estimated using a Vickers microindentation induced-fracture testing at distances of 15 and 30 m from the surface, applying four loads (0.49, 0.98, 1.96 and 2.9 N). The microcracks generated at the corners o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…(5) and (6), which can be used to obtain the diffusion stress through thermal stress finite element method. The diffusion coefficient of boron in DAZ is as follows [15] : 1 9 116 kJ mol 1.7 10 exp( ) [16] .According to Eq. (4) and (7), the thermal conductivity and CET of DAZ are 2.04×10 -7 W/(m·K) and 0.577×10 -6 /°C, respectively.…”
Section: Advances In Engineering Research Volume 118mentioning
confidence: 99%
“…(5) and (6), which can be used to obtain the diffusion stress through thermal stress finite element method. The diffusion coefficient of boron in DAZ is as follows [15] : 1 9 116 kJ mol 1.7 10 exp( ) [16] .According to Eq. (4) and (7), the thermal conductivity and CET of DAZ are 2.04×10 -7 W/(m·K) and 0.577×10 -6 /°C, respectively.…”
Section: Advances In Engineering Research Volume 118mentioning
confidence: 99%
“…The boride incubation times were deduced for a null boride layer thickness. It was shown that the higher boriding temperatures involve the shorter incubation times [22,27] as shown in Tables I and II. Figure 2 describes the temperature dependence of the two parameters β FeB (T ) and β(T ). It is noticed that these two parameters are linearly dependent on the boriding temperature and can be approximated by Eqs.…”
Section: Fe2b Bmentioning
confidence: 99%
“…where R is the universal gas constant (= 8.314 J/(mol K)), and T represents the absolute temperature in K. The reported values of the activation energies [22,27,29,30,34,36,37] of the borided steels are listed in Table IV together (20) and (21) can be rewritten as follows:…”
Section: Fe2b Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the RS superimpose with stresses present during in-service loading, the presence of compressive stresses enhances the fatigue life of components with significant tensile loads (Rodríguez-Castro et al, 2013). Moreover, the toughness of brittle materials can also be improved by compressive RS (Bermejo et al, 2006;Campos-Silva et al, 2010) which may also act as an effective barrier to crack initiation and propagation. Determination of RS is commonly done by employing powder diffraction methods which measure elastic strains present in the irradiated volume.…”
Section: Introductionmentioning
confidence: 99%